Analysis of fundraising strategies at the Zakat, Infaq and shadaqah Muhammadiyahs Institute (Lazizmu) district Sidoarjo: Analisis Strategi Fundraising Pada Lembaga Zakat Infaq dan Shadaqah Muhammadiyah (Lazizmu) Kabupaten Sidoarjo - Sayyidatunisa; Fitri Nur Latifah (Academia Open, 2021)
Fundraising is an importan activity for a nonprofit institution, because through this activity, the nonprofit organization can runout its program. This is also done by the Lazizmu district Sidoarjo, as an effort to realize its participation in community empowerment, and as to maximize potential social fund in Indonesia. The Study is conducted using a descriptive qualitative method of data collecting technique that are used in interview tevhniques, observation and documentations. The informant in this study is leader of Lazizmu Sidoarjo, chief of fundraising finance manager Sidoarjo, and fundraising volunteers. According to the study, there are 3 alternating strategies employed by Lazizmu Sidoarjo, namely dialogue fundraising involving the advent of fundraising volunteers, incidental ising, and socialization by mubaligh and various event, and than retention & development donor includes magazine management and services hotline and volunteers contact occupational ising after every seedling, and the last one is multichannel fundraising include telefundraising, the supply of cans in the AUM, with KLL at AUM and mosques and the use of social media.